A LEI 11.909/11 E POLÍTICAS EXTRAFISCAIS NA INDÚSTRIA DO GÁS NATURAL - Lanzillo, Anderson Souza da Silva; Moreira, Aron Abrahão; Fabricio, André Rodrigues (Revista Direito E-nergia, 2014)
A LEI 11.909/11 E POLÍTICAS EXTRAFISCAIS NA INDÚSTRIA DO GÁS NATURAL